The use of intramedullary reduction techniques in the treatment of irreducible intertrochanteric femoral fractures with negative medial cortical support - Huang, Xiaowen; Zuo, Qiang; Zhou, Hao; Lv, Tianrun; Liu, Jiuxiang (Frontiers in Surgery, 2024)
Objective: To explore the clinical efficacy of intramedullary reduction techniques for irreducible intertrochanteric femoral fractures with negative medial cortical support. Methods: A retrospective analysis was conducted on 69 patients with irreducible intertrochanteric femoral fractures with negative medial cortical support treated in the Department of Orthopedics at Jiangsu Province Hospital (The First Affiliated Hospital of Nanjing Medical University) from July 2019 to December 2021. Patients were divided into Group A and Group B. Group A (experimental group) consisted of 36 cases with an average age of 76.2 ± 5.9 years, while Group B (control group) comprised 33 cases with an average age of 76.6 ± 6.3 years. Group A received treatment using intramedullary reduction techniques, while Group B received treatment using traditional extramedullary reduction techniques. Both groups achieved anatomic reduction of the medial cortex or slight positive support. Surgical duration, intraoperative fracture reduction time, intraoperative bleeding, intraoperative fluoroscopy time, fracture reduction quality, fracture healing, postoperative neck-shaft angle loss, femoral neck shortening, and hip joint functional recovery score (FRS) were compared between the two groups. Results: All patients were followed up for an average of 13.8 months. Group A showed superior outcomes compared to Group B in surgical duration, intraoperative fracture reduction time, intraoperative bleeding, intraoperative fluoroscopy time, fracture reduction quality, fracture healing, postoperative neck-shaft angle loss, and femoral neck shortening (P<0.05). Hip joint function assessed by functional recovery score was better in Group A than Group B at 1 and 3 months postoperatively (P<0.05), with no significant statistical difference at other time points (P>0.05). Conclusion: For irreducible intertrochanteric femoral fractures with negative medial cortical support, intramedullary reduction techniques used during surgery demonstrated simplicity, significant reduction in surgical duration, decreased intraoperative bleeding, fewer amounts of intraoperative fluoroscopy, improved fracture reduction quality, and reduced surgical complexity. Further clinical research and application are warranted.